Role of DNA Repair Factor Xeroderma Pigmentosum Protein Group C in Response to Replication Stress As Revealed by DNA Fragile Site Affinity Chromatography and Quantitative Proteomics - Béresová, Lucie; Vesela, Eva; Chamrad, Ivo; Voller, Jiri; Yamada, Masayuki; Furst, Tomas; Lenobel, Rene; Chroma, Katarina; Gursky, Jan; Krizova, Katerina; Mistrik, Martin; Bártek, Jiří (Journal of proteome research, 2016)
Replication stress (RS) fuels genomic instability and cancer development and may contribute to aging, raising the need to identify factors involved in cellular responses to such stress. Here, we present a strategy for identification of factors affecting the maintenance of common fragile sites (CFSs), which are genomic loci that are particularly sensitive to RS and suffer from increased breakage and rearrangements in tumors. A DNA probe designed to match the high flexibility island sequence typical for the commonly expressed CFS (FRA16D) was used as specific DNA affinity bait. Proteins significantly enriched at the FRA16D fragment under normal and replication stress conditions were identified using stable isotope labeling of amino acids in cell culture-based quantitative mass spectrometry. The identified proteins interacting with the FRA16D fragment included some known CFS stabilizers, thereby validating this screening approach. Among the hits from our screen so far not implicated in CFS maintenance, we chose Xeroderma pigmentosum protein group C (XPC) for further characterization. XPC is a key factor in the DNA repair pathway known as global genomic nucleotide excision repair (GG-NER), a mechanism whose several components were enriched at the FRA16D fragment in our screen. Functional experiments revealed defective checkpoint signaling and escape of DNA replication intermediates into mitosis and the next generation of XPC-depleted cells exposed to RS. Overall, our results provide insights into an unexpected biological role of XPC in response to replication stress and document the power of proteomics-based screening strategies to elucidate mechanisms of pathophysiological significance.
Keywords: DNA vazebné proteiny; oprava DNA; Humans; Proteomics; lidé; Cell Cycle Checkpoints; Chromosome Fragile Sites; kontrolní body buněčného cyklu; replikace DNA; fragilní místa na chromozomu; proteomika; xeroderma pigmentosum; DNA Replication; DNA-Binding Proteins; Xeroderma Pigmentosum; DNA Repair; chromatografie afinitní; Chromatography, Affinity